Student Acceptance of E-learning to Improve Learning Independence in the Department of Computer Education - Mitra Pramita; R. Ati Sukmawati; Harja Santana Purba; Nuruddin Wiranda; Jajang Kusnendar; Mohd Samsu Sajat (Universitas Muhammadiyah Surakarta, 2022)
E-learning is an educational system that uses information technology in the learning process. One of the platforms that can be used in developing e-learning is Moodle. This research investigates the implementation of e-learning in the learning process in the Computer Education Department. The purpose of this research is to examine the use of E-learning in supporting the learning process. The respondents of this research are 130 active students of the Computer Education Department from the 2016 to 2018 Batches. The method used is a research questionnaire whose data are analyzed using the SPSS Statistics 25 program. This research shows no significant effect of student expectation on e-learning in supporting the learning process. Meanwhile, ease of e-learning, e-learning performance, and social influence for the benefit of e-learning have a significant effect on supporting the learning process and improve learning independence.